Polymer-tetrodotoxin conjugates to induce prolonged duration local anesthesia with minimal toxicity - Chao Zhao (Nature Portfolio, 2019)
There is interest in developing long-lasting local anaesthetics for a range of applications. Here, the authors report on the application of tetrodotoxin conjugated to amphiphilic biodegradable polymer to reduce systemic toxicity, achieve sustained release and investigate application as a local anaesthetic.